2019
DOI: 10.1155/2019/1739868
|View full text |Cite
|
Sign up to set email alerts
|

Antipathogenic Potential of a Polyherbal Wound-Care Formulation (Herboheal) against Certain Wound-Infective Gram-Negative Bacteria

Abstract: This study investigated antipathogenic efficacy of a polyherbal wound-healing formulation Herboheal against three multidrug-resistant strains of gram-negative bacterial pathogens associated with wound infections. Herboheal was evaluated for its quorum-modulatory potential against three different human-pathogenic bacteria, first in vitro through the broth dilution assay and then in vivo in the model host Caenorhabditis elegans. Herboheal at ≥0.1% v/v was able to inhibit (19–55%) in vitro production of quorum se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…These results indicate that it may be difficult for the pathogenic bacteria to develop complete resistance against polyherbal formulations like Triphala , but not impossible. Though our previous results on other polyherbal formulations ( Joshi et al , 2019 ; Patel et al ., 2019a ) and multicomponent crude plant extracts ( Joshi, 2019 ) have indicated that the probability of pathogens developing resistance against multi-component anti-virulence preparations is low, such a probability can certainly not be ruled out ( Kalia et al ., 2014 ; Singh, 2014 )…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…These results indicate that it may be difficult for the pathogenic bacteria to develop complete resistance against polyherbal formulations like Triphala , but not impossible. Though our previous results on other polyherbal formulations ( Joshi et al , 2019 ; Patel et al ., 2019a ) and multicomponent crude plant extracts ( Joshi, 2019 ) have indicated that the probability of pathogens developing resistance against multi-component anti-virulence preparations is low, such a probability can certainly not be ruled out ( Kalia et al ., 2014 ; Singh, 2014 )…”
Section: Resultsmentioning
confidence: 82%
“…After confirming the anti-infective activity of TF, we investigated (as described in Patel et al ., 2019a ) whether this formulation exerts any post-extract effect (PEE - https://doi.org/10.32388/359873 ) on the test pathogens i.e. whether the virulence-attenuating effect suffered by the parent bacterial culture is retained even in their daughter population never receiving any direct exposure to TF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the pathogenic strains mentioned above, all the gram-negative bacteria were multi-drug resistant, and the C. violaceum and S. marcescens strains used were beta-lactamase producers. Their antibiogram, along with culture conditions and growth media has previously been reported by us [Patel et al, 2019a]. Bird voices recorded at Dang Forest, Ahwa, Gujarat were obtained from Dr. Arun Dholakia, (Zoology Department, PTS Science College, Surat), and their frequency analysis was executed by performing a temporal frequency analysis (TFFT) using NCH WavePad v 7.13.…”
Section: Organismsmentioning
confidence: 99%
“…In vitro assays to study interaction of these two items with test bacteria with respect to bacterial growth, quorum-regulated pigment production, biofilm formation, and few other clinically relevant traits were also performed.CO and RA were procured from CDH and Sigma-Aldrich respectively. Methodology of the in vitro and in vivo assays was adopted from our previous publications (Joshi et al, 2019;Patel et al, 2019), which also contains details of the organisms used.Results explaining effect of CO and RA are presented through Figures 1-15, which indicate CO and RA both to be capable of attenuating virulence of pathogenic bacteria. Latter exerted activity at concentrations much lesser than that of CO.…”
mentioning
confidence: 99%